Orange-fleshed sweetpotato purée-based food applications, East Africa. Project profile. - International Potato Center (International Potato Center, 2019)
The increased demand from consumers in East Africa for convenient and healthy products needs to be matched by sweetpotato manufacturing technologies. This intervention will promote the commercialization of sweetpotato purée products and value addition in baked and fried products.